A Thematic Analysis of Students’ Listening Difficulties in an Indonesian EFL Senior High School Classroom - Julia Susanthy Hippy; Helena Badu; Farid Muhamad (Transbahasa, 2026)
Listening is one of the essential skills in learning English; however, many students still experience difficulties in listening comprehension. This study aimed to analyze the listening difficulties experienced by students at SMA Negeri 1 Limboto, focusing on three aspects: speech rate, vocabulary, and pronunciation. A qualitative approach was employed involving 21 students of Class X-1 as the research participants. Data were collected through interviews and analyzed using the thematic analysis framework proposed by Braun and Clarke (2006) which consists of six stages: familiarizing with the data, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and producing the report. The findings revealed that students experienced difficulties related to speech rate, limited vocabulary, and pronunciation. In addition, they encountered challenges in maintaining concentration, understanding unfamiliar words, and distinguishing between spoken and written forms of words. The findings indicate that speech rate, vocabulary, and pronunciation are the primary factors influencing students' listening comprehension. These results are expected to provide insights for English teachers in developing more effective listening instruction that addresses students' learning needs.